In silico investigation of pro-arrhythmic effects of azithromycin on the human ventricle - Liu, Yizhou (Biochem Biophys Rep, 2021)
The macrolide antibiotic azithromycin (AZM) is widely used for respiratory infections and has been suggested to be a possible treatment for the Coronavirus Disease of 2019 (COVID-19). However, AZM-associated QT interval prolongation and arrhythmias have been reported. Integrated mechanistic information on AZM actions on human ventricular excitation and conduction is lacking. Therefore, this study was undertaken to investigate the actions of AZM on ventricular cell and tissue electrical activity. The O'Hara- Virag-Varro-Rudy dynamic (ORd) model of human ventricular cells was modified to incorporate experimental data on the concentration-dependent actions of AZM on multiple ion channels, including I(Na), I(CaL), I(Kr), I(Ks), I(K1) and I(NaL) in both acute and chronic exposure conditions. In the single cell model, AZM prolonged the action potential duration (APD) in a concentration-dependent manner, which was predominantly attributable to I(Kr) reduction in the acute condition and potentiated I(NaL) in the chronic condition. High concentrations of AZM also increased action potential (AP) triangulation (determined as an increased difference between APD(30) and APD(90)) which is a marker of arrhythmia risk. In the chronic condition, the potentiated I(NaL) caused a modest intracellular Na (+) concentration accumulation at fast pacing rates. At the 1D tissue level, the AZM-prolonged APD at the cellular level was reflected by an increased QT interval in the simulated pseudo-ECG, consistent with clinical observations. Additionally, AZM reduced the conduction velocity (CV) of APs in the acute condition due to a reduced I(Na), and it augmented the transmural APD dispersion of the ventricular tissue, which is also pro-arrhythmic. Such actions were markedly augmented when the effects of chronic exposure of AZM were also considered, or with additional I(Kr) block, as may occur with concurrent use of other medications. This study provides insights into the ionic mechanisms by which high concentrations of AZM may modulate ventricular electrophysiology and susceptibility to arrhythmia.